Implementasi Transparansi Laporan Keuangan melalui Media Sosial Instagram pada LAZISNU Wonocolo Surabaya - Novie Andriani Zakariya; Nur ViVi Fidyaningrum; Nur Hayati Sufi; Salma Nabila; Razan Rafi Nashifan (Yayasan Literasi Sains Indonesia, 2025)
Distribution of funds at zakat institutions such as LAZISNU Wonocolo Surabaya is often faced with challenges of transparency and accountability, which can affect donor loyalty. it is important to implement practices that can increase donor confidence in fund management. This research aims to analyze the implementation of transparent and accountable fund distribution and its impact on donor loyalty at LAZISNU Wonocolo Surabaya. This research uses a descriptive approach with data collected through in-depth interviews with LAZISNU managers and donors, as well as analysis of documents related to fund distribution. The research results show that the implementation of transparency in financial reports and open communication with donors significantly increases donor trust and loyalty. Accountability in the use of funds also contributes to positive perceptions of donors towards the institution. It can be concluded that the application of the principles of transparency and accountability in the distribution of funds at LAZISNU Wonocolo Surabaya plays an important role in increasing donor loyalty. The recommendation for institutions is to continue to improve this practice in order to strengthen relationships with donors and support the sustainability of social programs.